2011
DOI: 10.5688/ajpe75354
|View full text |Cite
|
Sign up to set email alerts
|

Elective Course in Acute Care Using Online Learning and Patient Simulation

Abstract: Objective. To enhance students' knowledge of and critical-thinking skills in the management of acutely ill patients using online independent learning partnered with high-fidelity patient simulation sessions. Design. Students enrolled in the Acute Care Simulation watched 10 weekly Web-based video presentations on various critical care and advanced cardiovascular pharmacotherapy topics. After completing each online module, all students participated in groups in patient-care simulation exercises in which they pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 20 publications
2
52
0
1
Order By: Relevance
“…It encourages the development of communication, critical-thinking, problem-solving, and teamwork skills. 6,10,11 A unique feature of high-fidelity simulation is that disease states can be replicated to allow for standardization of student learning experiences. More importantly, students can practice and perfect their patient care skills at no risk to real patients.…”
Section: Introductionmentioning
confidence: 99%
“…It encourages the development of communication, critical-thinking, problem-solving, and teamwork skills. 6,10,11 A unique feature of high-fidelity simulation is that disease states can be replicated to allow for standardization of student learning experiences. More importantly, students can practice and perfect their patient care skills at no risk to real patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, these technologies were not without limitations. Barriers to implementing technology included student hesitation, 9,15,20 the need for technical support/oversight, 9,12,21,22 cost, 13,21,26 and resource utilization (eg, space, faculty time). 13,15,16,[19][20][21][22][23][24][25][26] …”
Section: Discussionmentioning
confidence: 99%
“…The studies showed that postsimulation quiz scores were significantly higher than presimulation scores (p#0.05); this includes naming and treating a condition, and medication administration. 13,14,16 Examination scores were reported in 1 study, which showed that the average examination score did improve, but not significantly. However, scores on data collection and interpretation questions on the examination did improve significantly (p,0.001).…”
Section: Human-patient Simulationmentioning
confidence: 92%
See 2 more Smart Citations